2018
DOI: 10.1007/s11356-018-3134-4
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of Fe3O4@MOF-100(Fe) magnetic microspheres for the adsorption of diclofenac sodium in aqueous solution

Abstract: In this research, the adsorptive removal of diclofenac sodium, one of the representative pharmaceuticals and personal care products, from aqueous solution using FeO@MOF-100(Fe) magnetic microspheres was studied for the first time. The FeO@MOF-100(Fe) microspheres exhibit strong magnetism and stability, which were observed as a core-shell structure. The maximum adsorption capacity of FeO@MOF-100(Fe) for diclofenac sodium can reach 377.36 mg L, which was higher than most of the adsorbents reported. The adsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(16 citation statements)
references
References 63 publications
2
12
0
2
Order By: Relevance
“…In the second step, weight loss of 2% and 5% in Fe 3 O 4 @AC and MIL-100(Fe) @Fe 3 O 4 @AC occurred in the range of 200–330 °C due to solvent removal and volatiles released by the decomposition of organic materials [7], respectively. In the third step, the main loss of 22.5% of MIL-100(Fe) @Fe 3 O 4 @AC total weight happened due to decomposition of H 3 btc molecules in the MIL-100(Fe) from 350 to 500 °C [48] and the weight of Fe 3 O 4 @AC remained constant at this temperature range. In the fourth step, weight loss of 16% and 12.5% in Fe 3 O 4 @AC and MIL-100(Fe) @Fe 3 O 4 @AC occurred in the range of 500–800 °C due to solvent removal the decomposition of organic compounds associated with Fe 3 O 4 and polycyclic compounds decomposition [49].…”
Section: Resultsmentioning
confidence: 99%
“…In the second step, weight loss of 2% and 5% in Fe 3 O 4 @AC and MIL-100(Fe) @Fe 3 O 4 @AC occurred in the range of 200–330 °C due to solvent removal and volatiles released by the decomposition of organic materials [7], respectively. In the third step, the main loss of 22.5% of MIL-100(Fe) @Fe 3 O 4 @AC total weight happened due to decomposition of H 3 btc molecules in the MIL-100(Fe) from 350 to 500 °C [48] and the weight of Fe 3 O 4 @AC remained constant at this temperature range. In the fourth step, weight loss of 16% and 12.5% in Fe 3 O 4 @AC and MIL-100(Fe) @Fe 3 O 4 @AC occurred in the range of 500–800 °C due to solvent removal the decomposition of organic compounds associated with Fe 3 O 4 and polycyclic compounds decomposition [49].…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that the adsorption of contaminants using only magnetite [45,46] is significantly lower than that of MOFs. In the same way, several researchers who incorporated magnetite into various materials observed a considerable increase in drug removal in an aqueous environment, and consistently achieved abysmal results in adsorption in pure magnetite [47]. Therefore, the study of adsorption of pure magnetite is omitted.…”
Section: Adsorption Of Pollutants On Materialsmentioning
confidence: 99%
“…Moreover, Fe 3 O 4 shows excellent separate characteristics due to its magnetic properties [ 28 ]. Therefore, it has been widely used in wastewater treatment in recent years [ 29 , 30 , 31 ]. In previous studies, Sun et al [ 32 ] prepared Fe 3 O 4 @C submicron rods by hydrothermal carbonization to remove MB in aqueous solution, but the larger particle size affects the comparison area and reduces the adsorption efficiency of MB.…”
Section: Introductionmentioning
confidence: 99%